The strange world of human sacrifice - Bremmer, Jan N. (Studies in the history and anthropology of religion, 2007)
Aztec human sacrifice as expiation / M. Graulich -- Human sacrifice in medieval Irish literature / J. Borsje -- Myth and ritual in Greek human sacrifice: Lykaon, Polyxena, and the case of the Rhodian criminal / J.N. Bremmer -- The early Christians and human sacrifice / L. Roig Lanzillotta -- Child sacrifice in ancient Israel: the status quaestionis / E. Noort -- Human sacrifice in ancient Egypt / H. te Velde -- Retainer sacrifice in Egypt and in Nubia / J. van Dijk -- Human sacrifice in India in Vedic times and before / A. Parpola -- Human sacrifice (puruṣamedha), construction sacrifice, and the origin of the idea of the "man of the homestead" (vāstupuruṣa) / H.T. Bakker -- Human sacrifice among the Konds / L.P. van den Bosch -- Human sacrifice in Japan / K. Harimoto -- Human sacrifice and self-sacrifice in China: a century of revelations / T.H. Barrett